P449 Cost Effectiveness of a Proactive Therapeutic Drug Monitoring Strategy in Patients with Inflammatory Bowel Disease Receiving Infliximab. (27th May 2021) - Doherty, J; Varley, R; Healy, M; Dunne, C; Mac Carthy, F; Mc Kiernan, S; Hartery, K; Kevans, D
Abstract: Background: Proactive therapeutic drug monitoring (TDM) has not demonstrated improved therapy outcomes compared with clinically-based dosing strategies. While the use of proactive TDM incurs additional assay-related costs this strategy may be cost-effective due to TDM-driven therapy dose de-escalation and discontinuation. Methods: We aimed to assess if proactive-TDM is cost-effective in clinical practice. A proactive TDM strategy was utilized in our unit with infliximab (IFX) and antibody-to-infliximab (ATI) levels assessed at trough in all inflammatory bowel disease(IBD) patients receiving IFX. Baseline demographics and IFX dosing schedules were documented. Patients were grouped based on disease activity status. Patients with IFX levels outside therapeutic range had dosing adjusted as appropriate. IFX dose adjustments were not protocolized and were at physicians discretion. IFX dosing regimens following proactive TDM were documented and net effect on IFX infusions number over the subsequent year extrapolated. Increase or decrease in drug-related costs on an annualized basis were estimated. Results: 108 patients were included. Median age 36 years. 46% were female. 36% had ulcerative colitis, 60% Crohn's disease. 35% were receiving concomitant immunomodulators. 56% were in remission at the time of TDM. 44%, 30% and 26% had IFX levels < 3 µg/mL, 3 – 7 µg/mL and > 7 µg/mL. IFX levels were significantly lower in patients with active disease compared with those in remission(p=0.008). Following proactive TDM assessment 37%, 11%, 36%, 13%, 2% and 1% of patients had no treatment change, therapy discontinuation, interval shortening, interval lengthening, dose increase and dose decrease respectively. Cost-effectiveness analysis focused on patients in remission (n=59). The use of proactive TDM-based IFX dosing resulted in a projected annualized reduction of 19.5 and 28.5 infusions due to IFX discontinuation and interval lengthening; the projected annualized increase in infusions was 39.1 and 4.3 due to IFX interval shortening and dose increase. This resulted in a net projected reduction of 4.7 IFX infusions per annum. Utilizing publicly available list prices for originator and biosimilar IFX and accounting for assay cost, projected cost savings resulting from proactive-TDM was 9105.0 and 6840.7 Euro per annum. Conclusion: Proactive TDM in IBD patients in remission resulted in a modest reduction in the projected annualized number of infusions in our unit with consequent minor drug-related cost savings. Proactive-TDM encouraged cost-effective prescribing of IFX, however, the effect was minor. The frequency at which proactive TDM should be performed and whether subsequent rounds of proactive-TDM would continue to deliver similar cost savings is uncertain.